Topical application of bFGF on acid-conditioned and non-conditioned dentin: effect on cell proliferation and gene expression in cells relevant for periodontal regeneration - Fernanda Regina Godoy Rocha; João Antônio Chaves de Souza; Morgana Rodrigues Guimarães-Stabili; José Eduardo Cezar Sampaio; Carlos Rossa Junior
Abstract Periodontal regeneration is still a challenge in terms of predictability and magnitude of effect. In this study we assess the biological effects of combining chemical root conditioning and biological mediators on three relevant cell types for periodontal regeneration. Material and Methods: Bovine dentin slices were conditioned with 25% citric acid followed by topical application of basic fibroblast growth factor (bFGF, 10 and 50 ng). We used ELISA to assess the dynamics of bFGF release from the dentin surface and RT-qPCR to study the expression of Runx2, Col1a1, Bglap and fibronectin by periodontal ligament (PDL) fibroblasts, cementoblasts and bone marrow stromal cells (BMSC) grown onto these dentin slices. We also assessed the effects of topical application of bFGF on cell proliferation by quantification of genomic DNA. Results: Acid conditioning significantly increased the release of bFGF from dentin slices. Overall, bFGF application significantly (p<0.05) increased cell proliferation, except for BMSC grown on non-conditioned dentin slices. Dentin substrate discretely increased expression of Col1a1 in all cell types. Expression of Runx2, Col1a1 and Fn was either unaffected or inhibited by bFGF application in all cell types. We could not detect expression of the target genes on BMSC grown onto conditioned dentin. Conclusion: Acid conditioning of dentin improves the release of topically-applied bFGF. Topical application of bFGF had a stimulatory effect on proliferation of PDL fibroblasts, cementoblasts and BMSC, but did not affect expression of Runx2, Col1a1, Bglap and fibronectin by these cells.